A prevalência da cárie dentária em crianças com paralisia cerebral - Medeiros, Kátia Linhares da Ponte (2019)
Given the relevance of oral health care in the context of comprehensive health care for children with cerebral palsy (CP) and understanding the role of dental caries as a prominent factor among oral diseases, there was the need to study this population group. The objective was to analyze prevalence of dental caries and related factors. A quantitative epidemiological cross-sectional study was carried out with 102 people: 51 children with cerebral palsy and their 51 main caregivers served by the Center for Early Intervention and Treatment (Núcleo de Tratamento e Estimulação Precoce – NUTEP). The deft/DMFT index was used to assess dental caries status. A formulary was also administered to the children’s caregivers to assess factors that may be related to dental caries in the analyzed group. The obtained data were described as absolute and percentage frequency and analyzed using chi-squared and Fisher’s Exact tests. The Statistical Package for the Social Sciences version 17.0 for Windows was used with a confidence interval of 95%. The household income of most children (52.97%) was low and only 25.49% of the children performed oral hygiene 3 times or more a day. A total of 58.82% of the caregivers reported difficulties in performing children’s oral hygiene and caregiving burden was mostly cited (41.86%) as a factor that limited the frequency of children’s oral hygiene. In all, 69.41% of the children who received oral feeding consumed sugary foods 3 times or more a day and 45.09% of the analyzed children were never taken to a dental appointment. A total of 42.85 % of the children who had already consulted with a dental surgeon did it in public health services of primary and secondary care. Regarding the prevalence of caries, 37.25% of the children had had caries experience and 33.33% presented untreated caries. As for severity, the mean DMFT score was 0.47 and the mean deft score was 1.29. There was a significant positive relationship between deft index and presence of factors that limited oral hygiene frequency (p = 0.013) and between DMFT index and presence of intellectual disability (p = 0.048) and preferred place for dental care (p = 0.013). In conclusion, one third of the analyzed children had decayed tooth and hence needed real professional oral health care. In addition, there were factors related to the presence of intellectual disability, the existence of limitations in oral hygiene and dental services used that may have contributed to the development of dental caries in the children. Therefore, public policies are needed to facilitate access to oral health services focused on health promotion and disease prevention and treatment. Given that, dental surgeons should be included into the early intervention and rehabilitation multidisciplinary team responsible for routinely following the children.